(untitled) (Revista cientifica In Vestigium Ire, 2021)
This article seeks to determine how through the implementation of a business structure the vision of the producers of the Cooperativa Agraria Cacaotera, “La Nueva Gema” in the municipality of Muzo (Boyacá), who wish to take a step forward and move from producers to marketers and transform cocoa into chocolate-based products, to improve their income and quality of life. The article shows the result of the School Research Project (PIE) 019 “Structuring a vision of the business model for the producers of the Cooperativa de Cacao de Muzo”. Belonging to the School of Administrative, Accounting, Economic and Business Sciences (ECACEN). For this, a descriptive and participatory methodology was applied, with a mixed approach, sources of information of primary and secondary origin, which allowed, through market research, to carry out an analysis of the sector and to identify the most preferredcocoa-based products with which seeks to promote this initiative in a region with very low socio-economic conditions, so it is proposed to apply an inclusive business model, seeking to generate a broad value proposition that involves all actors in the value chain (producer, customer, employee ), for which support will be required from the private, governmental, non-governmental sector, academy and the community in general in the generation of incomes and shared benefits between the parties.